PELATIHAN PENGGUNAAN STRATEGI HÖR-SEHEN DALAM MENINGKATKAN KEMAMPUAN MEMAHAMI TEKS BAGI GURU BAHASA JERMAN DI KOTA AMBON - Tomasouw, Jolanda; Marantika, Juliaans E. R.; Wenno, Eldaa Crystle; Noya van Delzen, June Carmen (Universitas Pattimura, 2024)
Hör-Sehen is a strategy that combines what is heard and what is seen, or what is called an audio-visual technique, making it easier for students to understand the content of the text. This community service aims to prepare teachers through training on the use of the Hör-Sehen strategy for improving text comprehension skills for German language teachers. In addition, this training is very appropriate to be implemented as a strategy to be used by teachers not only in listening skills but as a combination of what is heard and what is seen. Thus, teachers can apply it to the teaching and learning process in the classroom. The PKM activities carried out by the team for German language teachers in Ambon City are expected to help teachers improve students' understanding of German texts.